Polyphony as intersectional inquiry and praxis: Wendy Delorme's Le Corps est une chimère. (1st September 2022) - Schaal, Michèle A.
Abstract : This article posits Wendy Delorme's 2018 novel Le Corps est une chimère as an illustration of how intersectionality, as a theory and praxis, (re)centers those in the margins to better understand human societies, just as it simultaneously challenges any hegemonic system. Building on Patricia Hill Collins and Sirma Bilge's definition of intersectionality, I first examine Delorme's portrayal of heteropatriarchal violence as a form of intersectional critical inquiry. Le Corps est une chimère provides readers with an acute understanding, through a variety of situated standpoints, of how, under that system, gender-based, homophobic, classist, or racist violence are all interconnected. Next, I consider Delorme's writing as an intersectional critical praxis. Deploying polyphonic literature as a Wittigian Trojan Horse, Delorme decenters heteropatriarchy. She forces all readers to empathize and identify with marginalized folx and communities, therefore fostering solidarity, a necessary step, for theorists and activists of intersectionality, to effectively carry out social justice.